A Practical Approach to Combined Transcatheter Mitral and Tricuspid Valve Intervention - Burke, Lucas; Hassanin, Magdi; Ong, Geraldine; Fam, Neil (Frontiers in Cardiovascular Medicine, 2021)
Concomitant tricuspid regurgitation (TR) is common in patients with mitral regurgitation (MR). While current guidelines recommend repair of both valves at the time of surgery when feasible, high risk patients are often undertreated, leading to significant morbidity and mortality. With advances in transcatheter edge-to-edge repair (TEER) devices and technique, combined TEER for treating significant MR and TR has emerged as a new tool for heart failure management. Recent evidence has shed light on which patients with severe TR should be targeted for transcatheter intervention either in isolation or in combination with a MV TEER procedure and allows for expanded treatment options in patients who otherwise would be limited to medical management. Technological advancements remain ahead of robust clinical data, and thus randomized clinical studies in patients with severe MR and TR will be instrumental in determining the best approach in treating these patients with transcatheter therapies.